Medical Eligibility as a Predictor of Continued Copper Intrauterine Device (IUD-Cu) Use: A Correlational Analysis - Suazini, Esa Risi; Al Maki, Wikky Fawwaz; Cahyati, Widya Hary (Media Publikasi Cendekia Indonesia, 2025)
Approximately 60% of acceptors expressed dissatisfaction with contraceptive counseling services, which has resulted in a 0.7% decrease in modern contraceptive use in the last five years. One important factor in the sustainability of contraceptive use is the suitability of the acceptor's medical condition. This study aimed to determine the relationship between medical appropriateness and plans for continued use of the IUD-Cu. This study used a descriptive correlational design with a cross-sectional approach. Data were collected through structured interviews using a Medical Eligibility Criteria (MEC) application-based questionnaire. This application was created by WHO based on the 5th edition of the 2015 MEC for Contraceptive use guidebook. The sample was purposively selected, and 280 IUD-Cu acceptors were obtained. Univariate analysis was performed with frequency distribution and categorization of medical eligibility, while bivariate analysis used Chi-Square test and Prevalence Ratio (PR) with 95% CI. The results showed that 92.9% of acceptors were medically fit to use IUD-Cu, while 7.1% were not fit. A total of 12.1% of acceptors planned to change contraceptives. There was a significant association between medical eligibility and plans to continue using the IUD-Cu (p = 0.000; PR = 3.077; 95% CI: 1.574-6.015), indicating that medically eligible acceptors had 3.077 times greater potential to continue using the IUD-Cu than those who were not eligible. Therefore, it is recommended to optimize pre-installation screening of IUD-Cu with medical criteria-based tools so that the sustainability of contraceptive use can be maintained and women's reproductive rights are maximally fulfilled.